Development of the rice-powder manufacturing system using underwater shock wave - Shimojima, K; Miyafuji, Y; Naha, K; Higa, O; Matsubara, R; Higa, K; Higa, Y; Matsui, T; Takemoto, A; Tanaka, S; Maehara, H; Itoh, S (The International Journal of Multiphysics, 2012)
Self-sufficiency in food is very low (about 40%) in Japan. Therefore, the rice powder is paid to attention because it can be processed to the udon (noodle) and bread etc. We has already developed the rice-powder disintegrator using the underwater shock wave by the electrode. But it has not been cleared what is the most suitable pressure vessel. The purpose of this study is to investigate the most suitable configuration of the pressure vessels for manufacturing the rice-powder using the underwater shock wave. Experimental conditions to manufacture the rice-powder (particle size is 100 μm) is clarified using this device. Moreover, the manufacturing efficiency of the rice-powder, the relation between the number of the shock wave generation and the grain degree of rice-powder is clarified.